Enhancing Microgrid Protection Through Adaptive Decentralized Relay Coordination: A Solution to Blinding and Sympathetic Tripping - Sujatha Balasubramanian; J. Preetha Roselyn; Prabha Sundaravadivel (IEEE Access)
Integrating Distributed Energy Resources into microgrids modifies the network’s system parameters and causes it to exhibit behaviour, particularly during fault conditions. This is due to the greater variations in current direction and magnitude. When a microgrid runs in autonomous mode, Distributed Generators result in a reduced short circuit current compared to a system working in grid-connected mode. Microgrid protection issues, namely, blinding of protection, sympathetic tripping, and bidirectional power flow, occur in the power network under such circumstances. The impact of microgrid protection issues and changes in fault current leads to variations of overcurrent relay settings, their operating time and relay pair coordination. This paper presents an adaptive decentralized protection technique for ensuring the coordination of overcurrent relays in a microgrid network, even under situations of uncertainty. This method involves estimating the relay settings in the microgrid without considering DG and establishing relay coordination. The fault currents of the system, including DG, are calculated using the Thevenin equivalent circuit. These currents are derived from the perspective of the relay by analyzing the current and voltage measured at relay position before system fault. The proposed adaptive decentralized protection is developed and implemented in an IEEE-modified 9-bus and 14-bus system. The proposed method of coordination is compared against the conventional relay coordination method. The simulation studies are carried out in the MATLAB simulation and Digsilent Powerfactory 2023 version. The simulation results demonstrate effectiveness of proposed decentralized adaptive protection strategy in addressing all protection issues in the DG-integrated microgrid network.